ANALISIS STRATEGI PEMASARAN KAIN TENUN RUMAH PRODUKSI MEKAR SARI DI KECAMATAN RABA KOTA BIMA - Mardiah, Ainun; Sjah, Taslim; Sahidu, Arifuddin (JURNAL AGRIMANSION, 2023)
This research aims to analyze the marketing strategies of Mekar Sari's Handwoven Fabric. The method used in this research is descriptive. The unit of analysis in this research is the Mekar Sari production house. The research area was determined using purposive sampling considering that Mekar Sari's fabric consumers are spread across the Raba District. The types of data used are qualitative and quantitative. The data sources used in this research are primary and secondary data. The variables in this research are place, price, product, and promotion. The data analysis techniques used are SWOT analysis, IE analysis, and QSPM analysis. The research results indicate that there are 3 priority strategies to be implemented, namely building brand identity, offering discounts to recruit agents in strategic locations, and expanding the market.